2020
DOI: 10.1002/dta.2820
|View full text |Cite
|
Sign up to set email alerts
|

Phase I metabolites (organic acids) of gamma‐hydroxybutyric acid–validated quantification using GC–MS and description of endogenous concentration ranges

Abstract: Gamma‐hydroxybutyric acid (GHB) is a sedative drug used in drug‐facilitated crimes. Its detection window is very short. GHB undergoes intensive phase I metabolism to organic acids (glycolic acid, succinic acid, dihydroxybutyric acids). These could be potential analytical targets to broaden the detection window. The aim of the present study was to enable the detection of endogenous levels of these metabolites in biological samples (blood and urine). A gas chromatographic–mass spectrometric method using liquid–l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
39
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(62 citation statements)
references
References 57 publications
18
39
2
Order By: Relevance
“…Still, without final structural characterization, it cannot be unambiguously confirmed, that it is actually a derivative of glycolic acid and whether it might be useful as such to extent the detection window of GHB. As already discussed in former studies, using glycolic acid alone most likely lacks specificity as a proof for GHB intake given its presence in all samples and possible other sources for increased concentration, such as e.g., ethylene glycol poisoning [13,15]. In our data set, dihydroxybutyric acid, the oxidation product formed through alpha-and beta-oxidation of GHB was indicated as statistically significant after GHB intake.…”
Section: Organic Acids (Glycolate Succinylcarnitine Dihydroxybutyrate)mentioning
confidence: 61%
See 4 more Smart Citations
“…Still, without final structural characterization, it cannot be unambiguously confirmed, that it is actually a derivative of glycolic acid and whether it might be useful as such to extent the detection window of GHB. As already discussed in former studies, using glycolic acid alone most likely lacks specificity as a proof for GHB intake given its presence in all samples and possible other sources for increased concentration, such as e.g., ethylene glycol poisoning [13,15]. In our data set, dihydroxybutyric acid, the oxidation product formed through alpha-and beta-oxidation of GHB was indicated as statistically significant after GHB intake.…”
Section: Organic Acids (Glycolate Succinylcarnitine Dihydroxybutyrate)mentioning
confidence: 61%
“…The current analytical method was not optimized for chromatographic separation of GHB or its metabolites and was unable to separate the two isomers 2,4-and 3,4-dihydroxybutyric acid. Previous studies though indicated different concentrations of both isomers in humans, with higher concentrations of the 3,4-isomer in blood and urine [15].…”
Section: Organic Acids (Glycolate Succinylcarnitine Dihydroxybutyrate)mentioning
confidence: 90%
See 3 more Smart Citations